al haststu ala ad-dhabt wa al-hirasah li al-hadist wa ilmi al-lughah: Encourage the Control (dhabt) and Guarding of Hadith and Linguistics - Salah, Hamed Ahmed Yahya ali (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
The aim of the research is to study and investigate the book “Urging the Control and Guarding of Hadith and Linguistics” by the scholar Yahya bin Al-Hussein bin Al-Qasim bin Muhammad, d. 1099 AH, in recognition, and it has been followed in this research. The descriptive, inductive and analytical approach to the author’s statements compared to the statements of other scholars, while attributing the issues to their sources and commenting on what needs comment and clarification, and the research and investigation reached a set of results: The book contained important benefits related to the most important issue related to the science of the Prophet’s hadith in particular and the Sharia sciences in general, which are The issue of control related to books of hadith and other things, and the distortion and distortion that results from it, which leads to overturning texts and diverting them from their intended meaning, and warning about the danger of distortion and distortion occurring in books, and the importance of controlling books when reading and making sure to acquire high-quality copies and read them to specialized scholars, and approved books in Hadith and its grading, the importance of relying on the principles and not on abbreviations, and seeking help from books that control the hadith, language, names, places, countries, men’s names, surnames, and titles, and so on.